Strategies in early clinical development for the treatment of basic defects of cystic fibrosis. (2nd April 2016) - Dhooghe, Barbara; Haaf, Jérémy Boris; Noel, Sabrina; Leal, Teresinha
ABSTRACT: Introduction : Twenty-six years after the identification of the gene responsible for cystic fibrosis (CF), controversies still surround the pathogenesis of the disease that continues to burden and shorten lives. Therefore, finding effective therapeutic strategies that target the basic defect of CF is crucially needed. Areas covered : This review offers a comprehensive survey of fundamental therapies in early stages of development for the treatment of CF. The first part describes recent strategies targeting the basic defect either at the gene or at the transcript level. The second part summarizes a panel of novel strategies targeting protein repair. The third part reports strategies targeting non-CFTR channels. Expert opinion : Recent major breakthroughs in CF therapy have been made, raising hope to find a cure for CF. Apart from Vertex corrector and potentiator molecules (lumacaftor, ivacaftor, VX-661) and from ataluren, used to correct nonsense mutations, most compounds being currently tested are in very early (I-II) phases of development and definitive clinical results are keenly expected. Among the broad list of molecules and strategies being tested, the QR-010 compound and inhibitors of phosphodiesterase type 5 (sildenafil, vardenafil) could reveal a strong potentiality as therapeutic candidates to cure CF.